STUDI TENTANG PENGARUH TECHOPRENEURIAL LEARNING TERHADAP TECHNOPRENEURSHIP INTENTION SISWA SMKN SE-KOTA PALEMBANG - Izza Aprilianti Wardani; Amir Machmud; Suwatno - (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
ABSTRACTThis study aims to analyze the effect of technopreneurial learning on technopreneurship intention of bussiness and marketing studies of vocational high school students of Palembang city. Technopreneurial learning is measured through contextual learning, personal & social emergence, negotiated enterprise. Technopreneurship intention is measured through indicators of desires, preferences, plans and behavior expectations. This research method used was an explanatory survey using a questionnaire as an instrument using a Likert scale 1-5 with data collection techniques through a questionnaire distributed to vocational high school students in Palembang as many as 217 students. Data analysis techniques using simple regression analysis. The results of the study indicate that there is an effect of technopreneurial learning on technopreneurship intention where the effect is positive and significant. This positive means that the more effective technopreneurial learning affect the higher of technopreneurship intentiion. Based on the results of the distribution of questionnaires found that technopreneurial learning is in the effective category and technopreneurship intention is in the high category. The findings of this study that technopreneurial learning affects the technopreneurship intention is 43%.Keywords:Technopreneurial learning, Technopreneurship intention